Study of the Success Criteria for Quantity Surveying Firms in Selangor - Lim, Hui Lin (2015)
Quantity surveyor ¡s one of the important parties in construction industry. As Malaysia is a developing Country, more construction projects are being carried out for the development, which causes the demand for quantity surveying firm increases. Thus, number of quantity surveying firms in Selangor is increasing to fulfil the demand in the market. Establishing a firm is not the critical part hut the important one is to make the firm to be successful. The aim for this research is to provide understanding about how to increase the chance of success for the quantity surveying firms in a competitive market. Three objectives are achieved to accomplish the aim. The objectives are to define successful quantity surveying firms, to investigate the success criteria for quantity surveying firms in Selangor, and to analyse the major success criteria for quantity surveying limits in Selangor. The research method used in this study is the survey method. Online survey and unstructured interviews arc carried out to collect information. The data obtained from the questionnaires are analysed using descriptive statistics and relevant significant t-tests. There are 33 respondents involved in giving feedback for this research. Successful quantity surveying firms is defined as the firms which provide the services that always achieve client’s satisfaction. There are ten success criteria identified, which are (1) resources and finance, (2) code of ethics and the way of performing task, (3) competency of consultants, (4) location of firm, (5) technology used to perform task, (6) social network and client relationship, (7) strategic planning in operating the firm, (8) communication and sharing information, (9) size and nature of firm, and (10) client’s satisfaction. The two major success criteria arc (I) client’s satisfaction and (2) code of ethics and the way of performing tasks. The outcomes from this study help the firm’s owners to achieve success in a simpler way by understanding the success criteria. As a result, this study provides some understanding and guidelines to increase chance of success for the quantity surveying firms in Selangor.